Estándar de Gestión de Proyectos para el Diseño de Cursos Virtuales para la Empresa Digital Commerce Consulting, DiCommerC S.A. - Caravaca-Corrales, Andrés (Instituto Tecnológico de Costa Rica, 2016)
Digital Commerce Consulting, DiCommerC S.A. is a small company which provides products and services in four areas: marketing, innovation, entrepreneurship and professional project management. The company is looking for new strategies to differentiate itself from its competitors and is evaluating the possibility of creating a new business unit to manage virtual courses, design projects, and target corporate clients such as universities in local and international markets. The following Final Graduation Project (FGP), comprise the objective of developing a standard for project management for the design of online courses for Digital Commerce Consulting, DiCommerC S.A. This project addresses the risks and uncertainties inherent in creating a new business unit with limited industry experience. To address this problem, the project analyzes the actual situation of DiCommerC S.A. through general management interviews and business diagnostics designed by DIGEPYME office of Ministerio de Economía, Industria y Comercio (MEIC). In addition, it will incorporate a survey of professionals who manage projects for online education in five universities in Costa Rica in order to identify technical and project management processes that shape the life cycle of online course design. Finally, the project illustrates the standard for project management for online courses design including best practices from the standard of PMBOK®-Fifth Edition. This standard will allow the company to diminish the uncertainty relating the decision whether create or not create a new business unit.
Proyecto de Graduación (Maestría en Gerencia de Proyectos) Instituto Tecnológico de Costa Rica. Escuela de Ingeniería en Construcción, Escuela de Ingeniería en Computación, Escuela de Administración de Empresas, 2016.
Keywords: Curso virtual; Ciclo de vida; Estándar; MEIC; DIGEPYME